EVALUASI IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DALAM MEMBANGUN KEPRIBADIAN ISLAMI PADA SISWA DI SEKOLAH SDIT AL-KHAIRIYAH CITANGKIL - Romadan, Ade Imun (Institut PTIQ Jakarta, 2024)
This research aims to evaluate the implementation of Islamic Religious Education (PAI) in forming Islamic personalities in students at SDIT Al-Khairiyah Citangkil. This research uses a qualitative approach with an evaluative design that focuses on three main aspects: input (preparation and resources), process (implementation of learning), and output (impact on student personality). Data was collected through in-depth interviews, observation, documentation and questionnaires involving students, teachers, school principals and parents. The research results show that the implementation of PAI at SDIT Al-Khairiyah has gone well, although there are several challenges, such as the need to update learning materials to make them more relevant to current developments and the use of technology in learning. Religion-based extracurricular activities also make a significant contribution to the formation of students' Islamic character. Overall, religious education at this school has succeeded in encouraging positive changes in student behavior and morals, such as increasing discipline in worship, politeness, and caring attitudes towards others. However, there are still students who need more attention in consistently practicing religious teachings. This research suggests the importance of increasing collaboration between schools and parents as well as innovation in learning methods to achieve more optimal results in the formation of students' Islamic personalities